Aberrant DNA methylation of the p16, APC, MGMT, TIMP3 and CDH1 gene promoters in tumours and the surgical margins of patients with oral cavity cancer - Strzelczyk, Joanna Katarzyna (J Cancer, 2018)
Oral cavity cancer is a type of head and neck squamous cell carcinoma (HNSCC) and contributes to significant morbidity and mortality each year. An epigenetic pathway of transcriptional inactivation for many genes has been described in various cancers, including HNSCC. For our study, we selected genes for which silencing caused by hypermethylation can promote cancer development. In 75 primary HNSCC tumours and paired surgical margins, we investigated the methylation status of the p16, APC, MGMT, TIMP3 and CDH1 gene promoters by methylation-specific PCR after bisulphite treatment. The promoter methylation rates of p16, APC, MGMT, TIMP3 and CDH1 in tumours were 58.67%, 49.33%, 58.67%, 50.67%, and 57.33% and 50.67%, 41.33%, 37.33%, 42.67%, and 25.33% in the surgical margin, respectively. Our observations confirm the presence of epigenetic changes not only in the cancer cells, but also in the surrounding mucosa and represent a basis for further analysis to unravel these complicated issues. Appropriate cancer risk assessment based on epigenetic alterations in surgical margins may influence a patient's diagnosis and cure.